Coupling effects of tide and salting-out on perfluorooctane sulfonate (PFOS) transport and adsorption in a coastal aquifer. (August 2022) - Li, Congrui; Zhang, Chenming; Gibbes, Badin; Wang, Tao; Lockington, David
Highlights: PFOS transport in the coastal aquifer with salting-out effect considered is numerically studied. With salting-out effect included, PFOS injected from inland tends to be intercepted by the upper saline plume and discharges from aquifer with the tide-induced saltwater circulation. Salting-out reduces both peak discharge rate and plume dispersion of the land-derived contaminants Abstract: The adsorption of perfluorooctane sulfonate (PFOS) on sediments is thought to be enhanced by the 'salting-out effect' (SOE), which reduces contaminant solubility as water salinity increases. The process of salting-out has been observed for PFOS in surface estuaries and likely operates in 'subterranean estuaries', where tide-induced groundwater circulation creates a dynamic saltwater-freshwater mixing zone in the aquifer adjacent to the ocean. The presence of this dynamic interface between dense seawater and fresh groundwater modifies the flow path of land-derived organic contaminants. However, it is unclear how SOE combined with tidal forcing of salt water, affects the transport and fate of these contaminants in a subterranean estuary. Numerical studies of groundwater dynamics in a coastal aquifer are carried out using a modified version of SUTRA to investigate the behavior of PFOS, as it moves through an aquifer-ocean interface. Three adsorption scenarios are investigated: no adsorption and linear adsorption with a constant coefficient ( Kd ) and a salinity-dependent Kd (due to SOE). Without adsorption, point-injected PFOS moves and spreads as a plume around the margin of the tide-induced upper saline plume (USP). This is in agreement with previous studies showing that a contaminant plume follows the freshwater discharge path and exits the aquifer around the USP in the intertidal zone. The increase of tidal amplitude enlarges the USP, forcing the discharge points of freshwater and PFOS seaward. In the case of a constant Kd, PFOS concentration decreases in the groundwater as expected with an increase of PFOS residence time in the aquifer. The spatial distribution of the contaminant plume is similar to that of the 'no adsorption' case. In the case with the SOE, which enhances the solute adsorption in the saltwater zone, PFOS tends to be intercepted by the USP, concentrated at its center, and subsequently discharged with the tide-induced saltwater circulation. SOE reduces both peak PFOS discharge rate and plume dispersion. In addition, the PFOS flow path moves upward and the PFOS discharges above the USP. The findings highlight the potential importance of investigating the SOE of organic contaminants for benthic organisms when considering their transport and fate in tidally influenced coastal aquifers.